Analisis Komponen Fisik Terhadap Kemampuan Shooting Pada Permainan Sepakbola Siswa MAN 2 Kota Makassar - Herman Herman; Achmad Karim (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research aimed to find out: (1) the correlation between leg eye coordinationAnd shooting ability in soccer games; (2) the correlation between leg muscle  strength and shooting ability in soccer games; (3) the correlation between leg  power explosion and shooting ability in soccer games; (4)  the correlation betweenleg eye, leg muscle strength and leg power explosion on shooting ability in soccerfor the students of physical education department of MAN 2 Kota Makassar.  Thetotal sample of the research was 30 students using simple random sampling technique. Technique of data analysis was descriptive correlation, regressive  analysis on the significant level was α= 0,05 using SPSS version 21. The result of the research indicated that:  (1) There is a significant correlation between leg eye  coordination and shooting ability in soccer games, with a value of r= 0.751 (ρ < = 0.05); (2) There is a significant correlation between leg muscle strength and  shooting ability in soccer games, with a value of r =0.657 (ρ < = 0.05); (3) There is a significant correlation between leg power explosion and shooting ability in soccer games, with a value of r= 0.620(ρ < = 0.05); (4) There is a significant correlation simultneously between leg eye, leg muscle strength and leg  power  explosion  on  shooting  ability  insoccer  for  the  students  of  physical education department of MAN 2 Kota Makassar, with the determinant coefficient (R2) = 0.679 or 67.9 %